The influence of environmental conditions and hypochlorous acid (HOCl) fogging on the infectivity of H1N1 influenza virus - Kuan-Che Feng; Haijiao Liu; Anish Ghai; Juyi Li; Huiting Luo; Won-Il Lee; Steffen Mueller; Jerome Cymerman; Marcia Simon; Miriam Rafailovich (Elsevier, 2023)
The influence of different environmental factors on the infectivity of H1N1 influenza virus was measured. We found less than 1-log reduction when viruses were exposed to NaCl solutions up to 5 M or solutions with pH = 4 through 11 for one hour. The infectivity of the virus was sensitive to the solution temperature. A log reduction ranging from 2 to more than 6 was observed starting at 50 °C and spanning just 3 or 5 for 10- or 30 min exposures, respectively. Drying the virus in media on aluminum or polymer coupons for 48 h resulted in a log reduction of 4 when kept at room temperature, but less than one when kept at 4 °C or -20 °C. Log reduction greater than 6 occurred at room temperature after 3 days, but only 1-log reduction occurred at 4 and -20 °C after 6 days. Drying on different coinage achieved similar results, except for pennies, where more than 6-log reduction was observed after 24 h. HOCl was used to fog the aluminum and polymer surfaces, placed vertically, for 5 and 7.5 min to achieve a log reduction of 4 and for 6.5 respectively. Storage of opened solution containers for 9 months at ambient resulted in a decrease in chlorine concentration from 550 ppm to 240 ppm. Fogging with the old solution was still able to achieve a log reduction of 6.5 after 7.5 min fogging. The study indicates that exposure to common environmental conditions such as a wide pH range, high salinity, and low temperatures has only a minor effect on infectivity. which can persist for more than 5 days when dried on commonly encountered surfaces, allowing accumulation of infectious viral titre. Fogging with HOCl is an effective method of delivering disinfectants to large areas, achieving complete reduction of the viral titer on both horizontal and vertical surfaces.